SOSIALISASI TERHADAP ORANG TUA PENTINGNYA PENDIDIKAN KARAKTER DI SEKOLAH DASAR LINGKUNGAN RW 8 KELURAHAN MANDALA - Syahfitriani Ginting; Sri Hanipah; Rival Hanip (Fakultas Teknik Universitas Cenderawasih, 2022)
Character education in today's era is very important to be applied to elementary school children. Character education is an effort that is applied to instill religious, moral, ethical values ​​in elementary school children through science, assisted by parents, teachers, and the community. This service aims to socialize to parents as the first environment for a child to get an education, how important it is to instill character education values ​​starting at an early age and especially in children at elementary school age. This community service is carried out in RW 8, Mandala Village, Merauke District, Mareauke Regency. This activity is carried out in 3 parts where in each part it uses the lecture method and question and answer discussion with parents. The results of this training are 1) increased understanding of parents about the importance of character education for elementary school children. 2) the increasing desire of parents to implement character education for children in elementary schools